Cybernetics and organisational analysis; Towards a better understanding of Beer.' s Viable System Model - Brocklesby, John; Cummings, Stephen; Davies, John (School of Management Working Papers, 1991)
This paper describes a model - the Viable Systems Model - which purports to explain the more fundamental essence of what is required for effective organisation. The model draws on concepts from the science of cybernetics, and focusses on the fundamental objective of viability - the ability of a system to maintain a separate identity. The paper provides a description of cybernetics appropriate to the needs of those with backgrounds in management and organisational behaviour, and is intended to guide practitioners through elementary VSM analyses of real organisations and diagnosis of cybernetic weaknesses. The paper also attempts to bridge the divide which exists between the so-called 'hard' and 'soft' disciplines which strive. to extend our knowledge about organisations and improve managerial practice